2019
DOI: 10.1038/s41598-019-54928-y
|View full text |Cite
|
Sign up to set email alerts
|

Adeno-associated virus capsid protein expression in Escherichia coli and chemically defined capsid assembly

Abstract: Research and clinical applications of recombinant adeno-associated virus (rAAV) significantly increased in recent years alongside regulatory approvals of rAAV gene therapy products. To date, all rAAV vectors as well as AAV empty capsids are produced in eukaryotic cells. We explored a new route to generate AAV capsids with the aim to analyze capsid assembly in a chemically defined setting and pave the way for new production methods and applications based on AAV virus-like particles (VLPs). We generated these em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 51 publications
1
25
0
Order By: Relevance
“…As SEC-HPLC still reveals a near uniform capsomere peak we conclude, that partially digested VP1-J8 still remains in pentameric form together with intact VP1-J8 monomers and therefore are impossible to remove. The formation of truncation products of viral protein during the expression in E. coli has also been reported for adeno associated viral protein VP3 and might therefore also be a result of E. coli proteases [28] . Further research needs to be undertaken to minimize the formation of these digestion products, and how to remove the bound chaperons, but using protease inhibitors throughout the whole process instead of only during cell disruption, run at reduced temperature and addition of ATP to remove chaperones will likely solve the issue.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…As SEC-HPLC still reveals a near uniform capsomere peak we conclude, that partially digested VP1-J8 still remains in pentameric form together with intact VP1-J8 monomers and therefore are impossible to remove. The formation of truncation products of viral protein during the expression in E. coli has also been reported for adeno associated viral protein VP3 and might therefore also be a result of E. coli proteases [28] . Further research needs to be undertaken to minimize the formation of these digestion products, and how to remove the bound chaperons, but using protease inhibitors throughout the whole process instead of only during cell disruption, run at reduced temperature and addition of ATP to remove chaperones will likely solve the issue.…”
Section: Discussionmentioning
confidence: 64%
“…China approved E. coli produced VLP vaccines Hecolin® and Cecolin® showing high efficiency and safety and providing proof of concept for E. coli produced VLP vaccines [ 26 , 27 ]. Several modular and non-modular VLPs based on a variety of structural viral protein such as hepatitis B core antigen (HBcAg), papilloma major capsid protein L1, bacteriophage Qβ, adeno-associated virus structural protein VP3 and polyomavirus major capsid protein VP1 have been produced in E. coli [ 24 , 25 , 28 , 29 ]. One of the most advanced approaches is the platform technology using modularized murine polyomavirus major capsid protein VP1 [10] .…”
Section: Introductionmentioning
confidence: 99%
“…31 The particle size distribution obtained from DLS is only semiquantitative compared to microscopy and of low resolution. 50 , 96 , 97 , 98 Overall precision of the method is low, with repeatability reported as poor as 45% CV for capsid titer and 85% CV for aggregate content using multi-angle DLS. 31 Operated in batch mode, DLS is a non-destructive method with high throughput and commonly used in conjunction with static light scattering (SLS).…”
Section: Main Textmentioning
confidence: 99%
“…Subsequently it was shown that virus capsid, envelope and, sometimes, core viral proteins can form VLP structures. VLPs can be experimentally generated in the laboratory using recombinant viral proteins that are expressed in a range of expression systems including prokaryotic cells [6], yeast [7], insect cell lines [8,9], plants [10] and mammalian cell lines [11,12]. While VLPs are commonly produced using proteins(s) from a single virus type, chimeric VLPs can also be created by the assembly of structural proteins from different viruses [6].…”
mentioning
confidence: 99%